2015
DOI: 10.1002/2015jd023773
|View full text |Cite
|
Sign up to set email alerts
|

Snow‐borne nanosized particles: Abundance, distribution, composition, and significance in ice nucleation processes

Abstract: Physicochemical processes of nucleation constitute a major uncertainty in understanding aerosol‐cloud interactions. To improve the knowledge of the ice nucleation process, we characterized physical, chemical, and biological properties of fresh snow using a suite of state‐of‐the‐art techniques based on mass spectrometry, electron microscopy, chromatography, and optical particle sizing. Samples were collected at two North American Arctic sites, as part of international campaigns (2006 and 2009), and in the city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 97 publications
(124 reference statements)
1
56
0
Order By: Relevance
“…It can also be seen that the warmer-temperature-active INPs are more heat sensitive and that the effect is lost around −12 • C (Figure 2 and Figure S1); presumably, at colder temperatures INPs are a mix of heat-resistant organic and mineral INPs [12]. The size observations agree with previous work on freshwater INPs in Wales [31], marine INPs [17,20], precipitation [35][36][37], and recent studies showing that ice nucleating fungi and pollen release copious numbers of small (e.g., <15 nm) cell-free INPs [38][39][40]. (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…It can also be seen that the warmer-temperature-active INPs are more heat sensitive and that the effect is lost around −12 • C (Figure 2 and Figure S1); presumably, at colder temperatures INPs are a mix of heat-resistant organic and mineral INPs [12]. The size observations agree with previous work on freshwater INPs in Wales [31], marine INPs [17,20], precipitation [35][36][37], and recent studies showing that ice nucleating fungi and pollen release copious numbers of small (e.g., <15 nm) cell-free INPs [38][39][40]. (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…Similar observations are reported by Augustin-Bauditz et al [145], who investigated the ice nucleation behavior of particles consisting of a mixture of illite-NX and biological material washed of birch pollen grains. Nanometer-sized particles of biological and inorganic origin were found to be the most abundant particles in snow samples from different ecosystems [146].…”
Section: Examining the Role Of Aging Of Biological And Biogenic Ice Nmentioning
confidence: 99%
“…We used relatively simple tests such as filtration, heat treatment, and DNA analysis as well as droplet-freezing experiments for rapid screening of biogenic submicroscale-INPs in natural rainwater samples. Rangel-Alvarado et al 21. investigated the nanosized particles present in North American snow, an important form of precipitation, and characterized their physical, chemical, and biological properties using a suite of modern laboratory techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Their results illustrated that particles smaller than 200 nm are dominant and account for 38–71% all snow-borne particles. Such particles have relatively high freezing temperature, ranging on average from −19.6 ± 2.4 to −8.1 ± 2.6 °C with a mean freezing temperature of −17.2 ± 7.1 °C21. The results of chemical analysis of the nanosized fraction showed that they are mainly composed of amino acids, monomers and peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation